Anti-Stokes resonant x-ray Raman scattering for atom specific and excited state selective dynamics. (7th October 2016) - Kunnus, Kristjan; Josefsson, Ida; Rajkovic, Ivan; Schreck, Simon; Quevedo, Wilson; Beye, Martin; Grübel, Sebastian; Scholz, Mirko; Nordlund, Dennis; Zhang, Wenkai; Hartsock, Robert W; Gaffney, Kelly J; et al.
Abstract: Ultrafast electronic and structural dynamics of matter govern rate and selectivity of chemical reactions, as well as phase transitions and efficient switching in functional materials. Since x-rays determine electronic and structural properties with elemental, chemical, orbital and magnetic selectivity, short pulse x-ray sources have become central enablers of ultrafast science. Despite of these strengths, ultrafast x-rays have been poor at picking up excited state moieties from the unexcited ones. With time-resolved anti-Stokes resonant x-ray Raman scattering (AS-RXRS) performed at the LCLS, and ab initio theory we establish background free excited state selectivity in addition to the elemental, chemical, orbital and magnetic selectivity of x-rays. This unparalleled selectivity extracts low concentration excited state species along the pathway of photo induced ligand exchange of Fe(CO)5 in ethanol. Conceptually a full theoretical treatment of all accessible insights to excited state dynamics with AS-RXRS with transform-limited x-ray pulses is given—which will be covered experimentally by upcoming transform-limited x-ray sources.